Levitation of delocalized states at weak magnetic field: critical exponents and phase diagram - Kagalovsky, V. (Физика низких температур, 2013)
We study numerically the form of the critical line in the disorder–magnetic field phase diagram of the p–q
network model, constructed to study the levitation of extended states at weak magnetic fields. We use oneparameter
scaling, keeping either q (related to magnetic field) or p (related to energy) constant, to calculate two
critical exponents, describing the divergence of the localization length in each case. The ratio of those two exponents
defines the form of the critical line close to zero magnetic field.